(untitled) (Nativa, 2024)
One of the main causes of climate change and global warming is greenhouse gas emissions. Livestock makes up 15% of the world’s greenhouse gases (GHG), whereas maritime shipping accounts for 3%. Cattle can produce about 500 grams of methane a day per cow. This study demonstrates that livestock ships are an extremely high source of methane emissions. This study also offers innovative scientific techniques for lowering methane gas emissions from livestock ships, techniques that you, as researchers, scientists, environmentalists, and policymakers, can help implement. The MV Gelbray Express Livestock ship was selected to investigate the overall emissions generated by the main engine and the livestock on board. Main engine CO2 emissions and livestock CO2 equivalent emissions are theoretically calculated during 24-hour sailing under engine full load and livestock full capacity. The study revealed that livestock CO2 equivalent emissions account for 43% of the total CO2 emissions emitted by the engine and the livestock. ZELP (Zero Emissions Livestock Project) has patented a unique catalytic technique for capturing and neutralizing methane generated during enteric fermentation in ruminant animals such as cows to decrease livestock methane emissions. Theoretical results show that using the ZELP mask reduces CO2 equivalent emissions by 58 000 kg per day at a livestock capacity of 4000 cattle onboard the MV Gelbray Express Livestock ship. Keywords: climate change; international maritime organization; Zero Emissions Livestock Project. Redução das emissões de metano em navios de transporte de gado para mitigar as emissões de gases com efeito de estufa e promover a sustentabilidade marítima transporte futura RESUMO: Uma das principais causas das mudanças climáticas e do aquecimento global são as emissões de gases de efeito estufa. A pecuária representa 15% dos gases de efeito estufa (GEE) do mundo, enquanto o transporte marítimo é responsável por 3%. O gado pode produzir cerca de 500 gramas de metano por dia por vaca. Este estudo demonstra que os navios de transporte de gado são uma fonte extremamente alta de emissões de metano. Este estudo também oferece técnicas científicas inovadoras para reduzir as emissões de gás metano de navios de transporte de gado, técnicas que você, como pesquisadores, cientistas, ambientalistas e formuladores de políticas, pode ajudar a implementar. O navio de transporte de gado MV Gelbray Express foi selecionado para investigar as emissões gerais geradas pelo motor principal e pelo gado a bordo. As emissões de CO2 do motor principal e as emissões equivalentes de CO2 do gado são calculadas teoricamente durante a navegação de 24 horas sob carga total do motor e capacidade total do gado. O estudo revelou que as emissões equivalentes de CO2 do gado são responsáveis ​​por 43% das emissões totais de CO2 emitidas pelo motor e pelo gado. O ZELP (Zero Emissions Livestock Project) patenteou uma técnica catalítica exclusiva para capturar e neutralizar o metano gerado durante a fermentação entérica em animais ruminantes, como vacas, para diminuir as emissões de metano do gado. Resultados teóricos mostram que o uso da máscara ZELP reduz as emissões de CO2 equivalente em 58.000 kg por dia em uma capacidade de gado de 4.000 cabeças de gado a bordo do navio MV Gelbray Express Livestock. Palavras-chave: mudança climática; organização marítima internacional; Projeto Pecuária Emissão Zero.